Situation Report: Romania, 26 August 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu and PEC Discuss Plan Fulfillment in First Half of 1976 Efforts to Exploit Natural Resources Intensified Privileged Writers Versus Censorship Era Socialista Publishes Japanese CP Views on Marxism-Leninism Romania-Greek Economic Co-operation Expanding "Frankfurt - Bucharest Bank A.G." Established to Aid Trade with FRG